Renal Transplantation in Systemic Amyloidosis—Importance of Amyloid Fibril Type and Precursor Protein Abundance. Issue 2 (21st November 2012) - Pinney, J. H.; Lachmann, H. J.; Sattianayagam, P. T.; Gibbs, S. D. J.; Wechalekar, A. D.; Venner, C. P.; Whelan, C. J.; Gilbertson, J. A.; Rowczenio, D.; Hawkins, P. N.; Gillmore, J. D.
<x xml:space="preserve">Abstract</x> Renal transplantation remains contentious in patients with systemic amyloidosis due to the risk of graft loss from recurrent amyloid and progressive disease. Outcomes were sought among all patients attending the UK National Amyloidosis Centre who received a renal transplant (RTx) between January 1978 and May 2011. A total of 111 RTx were performed in 104 patients. Eighty‐nine percent of patients with end‐stage renal disease (ESRD) due to hereditary lysozyme and apolipoprotein A‐I amyloidosis received a RTx. Outcomes following RTx were generally excellent in these diseases, reflecting their slow natural history; median graft survival was 13.1 years. Only 20% of patients with ESRD due to AA, AL and fibrinogen amyloidosis received a RTx. Median graft survival was 10.3, 5.8 and 7.3 years in these diseases respectively, and outcomes were influenced by fibril precursor protein supply. Patient survival in AL amyloidosis was 8.9 years among those who had achieved at least a partial clonal response compared to 5.2 years among those who had no response (p = 0.02). Post‐RTx chemotherapy was administered successfully to four AL patients. RTx outcome is influenced by amyloid type. Suppression of the fibril precursor protein is desirable in the amyloidoses that have a rapid natural history.